2021
DOI: 10.1186/s12866-021-02179-1
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-β-lactamase and AmpC genes in Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa isolates from abattoir and poultry origin in Nigeria

Abstract: Background Gram-negative bacteria (GNB) including Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae represent the most relevant reservoir of resistance genes such as metallo-β-lactamase (MBL) and AmpC genes that give them the undue advantage to resist antimicrobial onslaught. This study aimed to investigate the occurrence of MBL (blaIMP-1, blaIMP-2, blaVIM-1, blaVIM-2) and AmpC (blaFOX, blaDHA, blaCMY, blaACC) resistance genes in aforementioned GNB collected from abattoir and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 40 publications
(38 reference statements)
2
16
4
Order By: Relevance
“…In this paper, we detected only one strain of K. pneumoniae carrying bla NDM-1 in Shandong poultry farms; the other four carbapenem resistance-related genes— bla KPC , bla IMP , bla VIM , and bla OXA48 —were not detected. As of this writing, in livestock and poultry breeding, a handful of articles on CRKP carrying bla KPC , bla IMP , bla VIM , bla OXA48 , and bla NDM have been reported in China and other countries ( Candan and Aksöz, 2015 ; Hamza et al, 2016 ; Köck et al, 2018 ; Zhai et al, 2020 ; Chaalal et al, 2021 ; Ejikeugwu et al, 2021 ; Elmonir et al, 2021 ). For poultry isolates studied in Egypt, 15% (15/100) were resistant to carbapenems: all of them were positive for bla NDM ( Hamza et al, 2016 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this paper, we detected only one strain of K. pneumoniae carrying bla NDM-1 in Shandong poultry farms; the other four carbapenem resistance-related genes— bla KPC , bla IMP , bla VIM , and bla OXA48 —were not detected. As of this writing, in livestock and poultry breeding, a handful of articles on CRKP carrying bla KPC , bla IMP , bla VIM , bla OXA48 , and bla NDM have been reported in China and other countries ( Candan and Aksöz, 2015 ; Hamza et al, 2016 ; Köck et al, 2018 ; Zhai et al, 2020 ; Chaalal et al, 2021 ; Ejikeugwu et al, 2021 ; Elmonir et al, 2021 ). For poultry isolates studied in Egypt, 15% (15/100) were resistant to carbapenems: all of them were positive for bla NDM ( Hamza et al, 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…In a study of chicken in Algeria, a CRKP rate of 16.02% (29/181) was detected, which is a higher rate than this study ( Chaalal et al, 2021 ); in addition, a rate of 10.53% of bla NDM was detected in broilers in Egypt (2/19) ( Elmonir et al, 2021 ). Research in Nigeria showed that of the 370 isolates collected from slaughterhouses, cows’ anuses, and poultry cloacas, 83.30% were found to be encoded by Metallo-β-lactamase genes (especially bla IMP-1 and bla IMP-2 ) of K. pneumoniae ( Ejikeugwu et al, 2021 ) . bla OXA48 was first discovered in Turkey, and the co-infection of NDM-1 and OXA-48 was found in the country 3 years later, with a detection rate of 8% (4/50) ( Candan and Aksöz, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, there are no new classes of antimicrobials in the pipeline, and so it is unlikely that any new classes of effective antimicrobials will be available for 10 years or more to treat infections caused by resistant Gram-negative bacteria [ 45 ]. MDR E. coli in food animals in Nigeria is becoming prevalent [ 50 , 51 ], and several papers have documented MDR E. coli in poultry and poultry products in the country [ 29 , 52 , 53 , 54 ]. The potential risk of spread of MDR to humans through poultry consumption has been established in a case control study conducted in Canada [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, horizontal gene transfer may inherit antibiotic-degrading enzymes (β-lactamases) from other bacteria [ 14 ]. Biofilm production may play a role in resistance as well [ 15 ], these resistance are mediated by AmpC genes ( bla FOX , bla DHA , bla CMY , and bla ACC ) which are prospective sources for the extensive dissemination of antibiotic resistance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%